Analysis of Critical Thinking Skills Through Guided Inquiry Learning Model on Reaction Rate Materials - Ningtiyas, Rahayu Ratih; Nasrudin, Harun (Universitas Negeri Malang, 2021)
This study aimed to analyze students' Critical Thinking Skills on the Reaction Rate materials through the Guided Inquiry Learning Model. This study was conducted in SMAN 1 Taman using a one-group pretest-posttest design. The data obtained were analyzed using the percentage, mean, n-gain, and t-test techniques. The research result shows that (1) The average percentage implementation of Guided Inquiry Learning Model syntax executed in phases 1,2,3,4,5 and 6 in a row is 94.17 percent; 98.61 percen; 100 percent; 98.96 percen; 100 percen; and 100 percen, with excellent criteria, (2) the percentage of students' activities who are actively involved and relevant to Guided Inquiry Learning Model is 94.45 percent at a meeting I and 97.78 percent at meeting II, (3) students' Critical Thinking Skills are complete in all components tested, namely interpretation, inference, analysis, and explanation with an average gained score of 0.82; 0.84; 0.77; and 0.91, and (4) there is a significant difference in the results of Critical Thinking Skills between before and after being given a Guided Inquiry Learning Model. The results showed that the Guided Inquiry Learning Model is effective in improving students' Critical Thinking Skills